The DSP handbook : algorithms, applications and design techniques - Bateman, Andrew, ....-; Paterson-Stephens, Iain, ....- (Harlow : Pearson education, 2002)
1. DSP - What is it? 2. Designing With DSP - What's required? 3. DSP Devices - What's inside? 4. DSP Systems - An Overview DSP Algorithm Toolbox - Making It Happen. 5. Applications Toolbox I- General Purpose. 6. Applications Toolbox Ii- Filter Design. 7. Applications Toolbox Iii- Spectral Analysis. 8. Applications Toolbox IV- Specialist Applications. 9. Theory Behind the Algorithms - How Do They Work? 10. Putting it all Together - Case Studies. Appendix 1- Useful trigonometric identities and series expansions. Appendix 2- Derivation of continuous signal correlation and spectral density functions from samples.
Keywords: Signal processing -- Digital techniques